Resolution of enthesitis by guselkumab and relationships to disease burden: 1-year results of two phase 3 psoriatic arthritis studies. - Mcgonagle, Dennis; Mcinnes, Iain B.; Deodhar, Atul; Schett, Georg; Shawi, May; Kafka, Shelly; Karyekar, Chetan S.; Kollmeier, Alexa P.; Hsia, Elizabeth C.; Xu, Xie L.; Sheng, Shihong; Agarwal, Prasheen; et al. (Rheumatology, 2021)
OBJECTIVE: To further characterize the effect of guselkumab, a selective IL-23p19-subunit inhibitor approved for PsA, on enthesitis and assess relationships between enthesitis resolution and patient status/outcomes. METHODS: Adults with active PsA despite standard therapies in the phase 3 DISCOVER-1 and DISCOVER-2 studies were randomized 1:1:1 to guselkumab 100 mg every 4 weeks (Q4W); guselkumab 100 mg at week 0, week 4, Q8W; or placebo through week 20 followed by guselkumab 100 mg Q4W. Independent assessors evaluated enthesitis using the Leeds Enthesitis Index (LEI; total score 0-6). Enthesitis findings through week 24 were pre-specified to be pooled across studies; post hoc and week 52 analyses also employed pooled data. RESULTS: Among 1118 randomized, treated patients in DISCOVER-1 and 2 who had ≥1 LEI site evaluated, 65% had enthesitis at baseline. These patients exhibited numerically more swollen and tender joints, systemic inflammation and impaired physical function than patients without enthesitis. Guselkumab Q4W and Q8W were superior to placebo in resolving pre-existing enthesitis at week 24 (45 and 50% vs 29%; both adjusted P = 0.0301). Enthesitis resolution rates continued to rise; 58% of guselkumab-randomized patients achieved resolution at week 52, including patients with mild (LEI = 1; 70-75%), moderate (LEI = 2; 69-73%) or severe (LEI = 3-6; 42-44%) enthesitis at baseline. Among guselkumab-randomized patients with resolved enthesitis at week 24, 42% achieved minimal disease activity at week 52, vs 17% of patients with unresolved enthesitis. CONCLUSION: Guselkumab resulted in higher proportions of PsA patients with resolved enthesitis by week 24, with maintenance of resolution rates through 1 year. As enthesitis confers greater disease burden, sustained resolution could portend better patient outcomes. CLINICAL TRIAL REGISTRATION: DISCOVER 1 (NCT03162796) and DISCOVER 2 (NCT03158285).
EVALuna2:474319